2000
DOI: 10.3354/meps206227
|View full text |Cite
|
Sign up to set email alerts
|

Reef fish assemblages: a re-evaluation using enclosed rotenone stations

Abstract: The reef fish assemblage at Orpheus Island, Great Barrier Reef, was examined using visual censuses and the ichthyocide rotenone. Small 3.5 m 2 quantitative rotenone samples, using a fine-mesh net to enclose the site, were compared with visual-point censuses (prior to the placement of the net), random-point censuses and strip censuses. Furthermore, the fishes collected inside and outside the net were examined to determine the relative efficiency of enclosed versus open rotenone samples. Rotenone samples compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
240
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(253 citation statements)
references
References 41 publications
6
240
1
6
Order By: Relevance
“…ACKERMAN & BELLWOOD (2000) observed that a significant proportion of the total number and biomass of fishes on the reef were not accounted for by visual census. Nevertheless, non-destructive techniques should be recommended whenever reef ecosystem conservation is at stake, due to their little environmental interference and the possibility of fish observation in their natural habitat .…”
mentioning
confidence: 95%
“…ACKERMAN & BELLWOOD (2000) observed that a significant proportion of the total number and biomass of fishes on the reef were not accounted for by visual census. Nevertheless, non-destructive techniques should be recommended whenever reef ecosystem conservation is at stake, due to their little environmental interference and the possibility of fish observation in their natural habitat .…”
mentioning
confidence: 95%
“…Before model fitting, we narrowed the size fraction used for analysis to the range of body sizes that can be surveyed effectively with underwater visual transects. Small fishes (&15 cm) are subject to poor detectability in visual surveys [30], hence we used the corresponding mass of 32 g as the lower size cut-off for inclusion in analyses (additional detail provided in [8]). Only three fish larger than 2048 g were observed across all surveys, hence we excluded them and set this mass as our upper cut-off.…”
Section: (B) Biomass Spectramentioning
confidence: 99%
“…While over half of the overrepresented families include reef fishes, such as butterflyfishes (Chaetodontidae), wrasses (Labridae), surgeonfishes (Acanthuridae), triggerfishes (Balistidae), and squirrelfishes (Holocentridae), more cryptic reef taxa, such as blennies and gobies, are highly underrepresented (Table 1). As blennies and gobies are among the most species-rich clades of reef fishes (Eschmeyer and Fricke 2015) with speciation rates that rival those of African rift lake cichlids ), this bias is not the result of rarity, but rather corresponds with another known bias: under-sampling small cryptic species during the collection of visual survey data (DeMartini and Roberts 1982, Ackerman and Bellwood 2000, Schmitt et al 2002. This detection bias extends beyond blennies and gobies in our results.…”
Section: Discussionmentioning
confidence: 99%